2013
DOI: 10.1080/10286020.2013.802687
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin decreases oxidative stress in mitochondria isolated from liver and kidneys of high-fat diet-induced obese mice

Abstract: Oxidative stress plays a key role in obesity and diabetes-related mitochondrial dysfunction. Mitochondrial dysfunction is characterized by increased oxidative damage, nitric oxide (NO) synthesis, and a reduced ratio of adenosine-5'-triphosphate (ATP) production/oxygen consumption. Curcumin represents a potential antioxidant and anti-inflammatory agent. In this study, our objective was to determine the effect of curcumin treatment on oxidative stress and mitochondrial dysfunction in high-fat diet (HFD)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 22 publications
4
34
0
2
Order By: Relevance
“…The mitochondria are the main target for many anticancer agents. CMN and QR have been shown to protect the mitochondria against various oxidative stress conditions (Karuppagounder et al 2013;Martínez-Morúa et al 2013). Our study was designed to enlarge the therapeutic window of CMN and QR to regulate the neurotoxic effects of Oxa exposure in isolated brain mitochondria of rat.…”
Section: Introductionmentioning
confidence: 98%
“…The mitochondria are the main target for many anticancer agents. CMN and QR have been shown to protect the mitochondria against various oxidative stress conditions (Karuppagounder et al 2013;Martínez-Morúa et al 2013). Our study was designed to enlarge the therapeutic window of CMN and QR to regulate the neurotoxic effects of Oxa exposure in isolated brain mitochondria of rat.…”
Section: Introductionmentioning
confidence: 98%
“…However, upon investigating the effect of curcumin treatment on oxidative stress and mitochondrial dys- function in HFD-induced obese mice, Martínez-Morúa et al (2013) have found no significant elevation in the liver mitochondrial respiration chain and nitric oxide synthesis rates. In our study, the hepatic mitochondrial pro-oxidant-antioxidant system was also not influenced by HFD, which may be related to unaffected mitochondrial respiration rate.…”
mentioning
confidence: 95%
“…In animal models, curcumin supplementation, which exerts antioxidative and antilipidemic effects, has been suggested as an alternative treatment against lipid accumulation and oxidative damage, as well as mitochondrial dysfunction in fatty liver (Ejaz et al 2009;Martínez-Morúa et al 2013). In our previous study, high dose curcumin supplementation (400 mg·(kg body mass) -1 ·day -1 for 8 weeks) to rats by means of gavage, has been found to decrease hepatic lipids in the HFD group (Oner-İyidog an et al 2013).…”
mentioning
confidence: 99%
“…As an alternative, a number of studies have demonstrated the protective effect of curcumin towards mitochondrial dysfunction and mitochondrial oxidative stress (Zhu, Chen et al 2004, Martinez-Morua, Soto-Urquieta et al 2013). Most research has been concentrated on neurodegenerative diseases and finding new therapeutics for Alzheimer’s (Zhang, Fiala et al 2006, Mishra and Palanivelu 2008).…”
Section: Discussionmentioning
confidence: 99%